Glycoconjugated Metallohelices have Improved Nuclear Delivery and Suppress Tumour Growth In Vivo - Song, Hualong; Allison, Simon J; Brabec, Viktor; Bridgewater, Hannah E; Kasparkova, Jana; Kostrhunova, Hana; Novohradsky, Vojtech; Phillips, Roger M; Pracharova, Jitka; Rogers, Nicola J; Shepherd, Samantha L; Scott, Peter (Angewandte Chemie (International ed. in English), 2020)
Monosaccharides are added to the hydrophilic face of a self-assembled asymmetric FeII metallohelix, using CuAAC chemistry. The sixteen resulting architectures are water-stable and optically pure, and exhibit improved antiproliferative selectivity against colon cancer cells (HCT116 p53+/+ ) with respect to the non-cancerous ARPE-19 cell line. While the most selective compound is a glucose-appended enantiomer, its cellular entry is not mainly glucose transporter-mediated. Glucose conjugation nevertheless increases nuclear delivery ca 2.5-fold, and a non-destructive interaction with DNA is indicated. Addition of the glucose units affects the binding orientation of the metallohelix to naked DNA, but does not substantially alter the overall affinity. In a mouse model, the glucose conjugated compound was far better tolerated, and tumour growth delays for the parent compound (2.6 d) were improved to 4.3 d; performance as good as cisplatin but with the advantage of no weight loss in the subjects.
Keywords: Glycoconjugates; HCT116 buňky; glykokonjugáty; Neoplasms; Proton Magnetic Resonance Spectroscopy; nádory; Metals; lidé; HCT116 Cells; kovy; glycoconjugates; nuclear delivery; hmotnostní spektrometrie s elektrosprejovou ionizací; antitumor agents; self-assembly; metallohelices; Spectrometry, Mass, Electrospray Ionization; protonová magnetická rezonanční spektroskopie; Humans